Lipocalin-2 is associated with FGF23 in WNT1 and PLS3 osteoporosis - Loid, Petra; Hauta-alus, Helena; Mäkitie, Outi; Magnusson, Per; Mäkitie, Riikka E. (Frontiers in Endocrinology, 2022)
Background: The pathogenic mechanisms of early-onset osteoporosis caused by WNT1 and PLS3 mutations are incompletely understood and diagnostic biomarkers of these disorders are limited. Recently, lipocalin-2 has been recognized as an osteokine involved in bone development and homeostasis. However, the role of lipocalin-2 in WNT1 and PLS3 osteoporosis is unknown. Objective: We aimed to investigate if plasma lipocalin-2 could be utilized as a biomarker for WNT1 and PLS3 osteoporosis and to evaluate the association between lipocalin-2 and other parameters of bone metabolism. Methods: We measured plasma lipocalin-2 in 17 WNT1 and 14 PLS3 mutation-positive patients and compared them to those of 34 mutation-negative (MN) healthy subjects. We investigated possible associations between lipocalin-2 and several bone biomarkers including collagen type I cross-linked C-telopeptide (CTX), alkaline phosphatase (ALP), type I procollagen intact N-terminal propeptide (PINP), intact and C-terminal fibroblast growth factor 23 (FGF23), dickkopf-1 (DKK1) and sclerostin as well as parameters of iron metabolism (iron, transferrin, transferrin saturation, soluble transferrin receptor and ferritin). Results: We found no differences in plasma lipocalin-2 levels in WNT1 or PLS3 patients compared with MN subjects. However, lipocalin-2 was associated with C-terminal FGF23 in WNT1 patients (r=0.62; p=0.008) and PLS3 patients (r=0.63, p=0.017), and with intact FGF23 in PLS3 patients (r=0.80; p<0.001). In addition, lipocalin-2 correlated with serum transferrin in WNT1 patients (r=0.72; p=0.001). Conclusion: We conclude that plasma lipocalin-2 is not altered in WNT1 or PLS3 mutation-positive subjects but is associated with FGF23 in abnormal WNT1 or PLS3 signaling and with iron status in abnormal WNT1 signaling.